KOMUNIKASI INTERPERSONAL PASANGAN USIA EMAS DALAM MEMPERTAHANKAN KELUARGA HARMONIS PADA PENSIUNAN ABRI DI KELURAHAN BAGAN MANUNGGAL - Sabrila, Riesty Nova; Rimayanti, Nita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Interpersonal communication is very important in maintaining household harmony. With this interpersonal communication, couples can find out how to form a good relationship with each other. in the subdistrict of Bagan Manunggal sub-district, in the chart, it turned out that there were still many elderly couples who were still in harmony and still surviving at an advanced age of marriage. from the phenomenon of divorce that occurs a lot around him but Abri's pensioners are able to maintain his marriage until the age of gold. The purpose of this study was to explain how interpersonal communication between golden age couples in maintaining a harmonious family with retired children in a single village unit.            The purpose of this study was to explain how interpersonal communication between golden age couples in maintaining a harmonious family in retired servants in the village section The research was conducted in the village of Bagan Manunggal, Bagan Sinembah District, Rokan Hilir Regency. This study uses descriptive qualitative research methods that explain and interpret existing data. Informants in this researcher are husband and wife. Techniques for collecting data using observation, interviews and documentation.The results of this study indicate that interpersonal communication by husband and wife has gone well. married couples always communicate in an effort to foster, maintain and strengthen their interpersonal relationships in the family to avoid problems that arise in the family which later can lead to divorce by considering 5 aspects: openness, empathy, positive attitude, supportive attitude and equality. Openness, where the married couple has shown their open attitude by trusting each other and being loyal to each other. Empathy, where husband and wife feel what is felt by each other. Positive attitude, husband has shown a positive attitude by giving good advice to his wife. Supporting attitude, husband and wife have shown an attitude of support by accepting and giving input to each other. Equality, where husbands and wives can chat with each other but can respect each other. Keyword : Interpersonal Communication, Harmonius Family